Interaction between Galectin-3 and Integrins Mediates Cell-Matrix Adhesion in Endothelial Cells and Mesenchymal Stem Cells - Sedlář, Antonín; Trávníčková, Martina; Bojarová, Pavla; Vlachová, Miluše; Slámová, Kristýna; Křen, Vladimír; Bačáková, Lucie (International journal of molecular sciences, 2021)
Galectin-3 (Gal-3) is a β-galactoside-binding protein that influences various cell functions, including cell adhesion. We focused on the role of Gal-3 as an extracellular ligand mediating cell-matrix adhesion. We used human adipose tissue-derived stem cells and human umbilical vein endothelial cells that are promising for vascular tissue engineering. We found that these cells naturally contained Gal-3 on their surface and inside the cells. Moreover, they were able to associate with exogenous Gal-3 added to the culture medium. This association was reduced with a β-galactoside LacdiNAc (GalNAcβ1,4GlcNAc), a selective ligand of Gal-3, which binds to the carbohydrate recognition domain (CRD) in the Gal-3 molecule. This ligand was also able to detach Gal-3 newly associated with cells but not Gal-3 naturally present on cells. In addition, Gal-3 preadsorbed on plastic surfaces acted as an adhesion ligand for both cell types, and the cell adhesion was resistant to blocking with LacdiNAc. This result suggests that the adhesion was mediated by a binding site different from the CRD. The blocking of integrin adhesion receptors on cells with specific antibodies revealed that the cell adhesion to the preadsorbed Gal-3 was mediated, at least partially, by β1 and αV integrins-namely α5β1, αVβ3, and αVβ1 integrins.
Keywords: kultivované buňky; Mesenchymal Stem Cells; Cells, Cultured; Human Umbilical Vein Endothelial Cells; Protein Binding; mezenchymální kmenové buňky; lidé; Humans; spoje buňka-matrix; krevní proteiny; endoteliální buňky pupečníkové žíly (lidské); Binding Sites; Cell-Matrix Junctions; Integrins; buněčná adheze; galektiny; carbohydrate; vazba proteinů; ADSC; integrin; Blood Proteins; integriny; HUVEC; vazebná místa; galectin; Cell Adhesion; Galectins